PENERAPAN METODE MDLC DALAM PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY UNTUK MENGENAL JENIS-JENIS SAMBAL INDONESIA - Kalvin Lee; Herman Herman (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Indonesia, a multicultural country, has a diverse cultural heritage, including sambal as an integral part of food culture. Sambal was originally made from traditional Indonesian ingredients such as pepper and ginger, then cayenne pepper became the main ingredient of sambal in Indonesia. Each region has its own version of chili sauce with differences in cooking and serving methods. Therefore, the research will create a learning media based on Augmented Reality with the aim of introducing the types of chili sauce in Indonesia more widely. The method used uses the MDLC method which will be tested through black box testing and Linkert scale analysis.